ANALYSIS OF FACTORS THAT INFLUENCE CUSTOMER LOYALTY IN WAPRES COFFEE - Febrian Reinaldy Siahaan; Junfrian Hangoluan Lumban gaol; Eka Mayastika Sinaga; Imelda Mardayanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the factors that influence customer loyalty at Wapres Coffee, focusing on Generation Z customers. The factors studied include product quality, service quality, price, and cafe atmosphere. This study uses a quantitative approach with a survey method. The research sample consisted of 100 respondents selected using a purposive sampling technique, with the criteria of having made at least two purchases and being among Generation Z. Data collection was carried out through a structured questionnaire with a 5-point Likert scale. Data analysis used Structural Equation Modeling based on Partial Least Square (PLS) with the help of SmartPLS 3.0. The results showed that product quality (t = 2.429; p = 0.015) and cafe atmosphere (t = 2.108; p = 0.036) had a positive and significant effect on customer loyalty. Conversely, service quality (t = 0.996; p = 0.320) and price (t = 1.226; p = 0.221) were not proven to have a significant effect on customer loyalty. Product quality is the most dominant factor in shaping customer loyalty, with a path coefficient of 0.351. An R-squared value of 0.727 indicates that the four independent variables can explain 72.7% of the variation in customer loyalty. This study confirms that consistent product quality and a comfortable cafe atmosphere are key to building and maintaining Generation Z customer loyalty at Wapres Coffee.